2016
DOI: 10.1186/s12906-016-1392-6
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids from piper longum protect dopaminergic neurons against inflammation-mediated damage induced by intranigral injection of lipopolysaccharide

Abstract: BackgroundAlkaloids from Piper longum (PLA), extracted from P. longum, have potent anti-inflammatory effects. The aim of this study was to investigate whether PLA could protect dopaminergic neurons against inflammation-mediated damage by inhibiting microglial activation using a lipopolysaccharide (LPS)-induced dopaminergic neuronal damage rat model.MethodsThe animal behaviors of rotational behavior, rotarod test and open-field test were investigated. The survival ratio of dopaminergic neurons and microglial ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
(35 reference statements)
1
21
0
Order By: Relevance
“…Although the present work focused on liquiritigenin as an RNF146 inducer and neuroprotective agent, further studies characterizing other inducers could shed further light on RNF146 induction mechanisms and their therapeutic potential. Piperlonguminine is of particular interest because this compound is brain-permeable and neuroprotective in rotenone and lipopolysaccharide animal models [ 27 ]. Its property to stimulate autophagy would be additional therapeutic advantege especially for neurodegenerative disease with abnormal protein aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the present work focused on liquiritigenin as an RNF146 inducer and neuroprotective agent, further studies characterizing other inducers could shed further light on RNF146 induction mechanisms and their therapeutic potential. Piperlonguminine is of particular interest because this compound is brain-permeable and neuroprotective in rotenone and lipopolysaccharide animal models [ 27 ]. Its property to stimulate autophagy would be additional therapeutic advantege especially for neurodegenerative disease with abnormal protein aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral administration of a single dose of LPS into the SN or striatum which are the most common regions for stereotaxic administration of LPS, induces degeneration of dopaminergic neurons in the SN and their neuronal projections to the striatum. Intranigral administration of 10 ​μg of LPS in rats induces a 50–80% reduction in the number of tyrosine hydroxylase (TH) positive cells in the SN compared to shams at 4 weeks post-treatment ( Bao et al., 2018 ; Chen et al., 2017 ; Fu et al., 2015 ; He et al., 2016a ; Wang et al., 2015a ). This lesion to the nigrostriatal pathway was illustrated by increased rotational behaviour in the apomorphine and amphetamine induced rotational test which was not evident in the sham group.…”
Section: Lps Models Of Pd: An Overviewmentioning
confidence: 99%
“…This lesion to the nigrostriatal pathway was illustrated by increased rotational behaviour in the apomorphine and amphetamine induced rotational test which was not evident in the sham group. Moreover, striatal dopamine was reduced by 34–50%, along with motor function which was assessed with the rotarod test, commonly used to evaluate motor skills based on the ability of the animals to maintain themselves on a rotating rod ( Bao et al., 2018 ; Chen et al., 2017 ; Fu et al., 2015 ; He et al., 2016a ; Wang et al., 2015a ). Furthermore, according to Choi et al.…”
Section: Lps Models Of Pd: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that the activity of superoxide dismutase (SOD) was enhanced in PD rat aer administration of PLA. [4][5][6][7][8][9] SOD plays a signicant role in protecting cells from oxidative stress and preventing neuronal apoptosis.…”
Section: Introductionmentioning
confidence: 99%